Pengembangan Media Question Card Interaktif Berbasis Mastery Peak untuk Meningkatkan Kemampuan Numerasi Siswa Kelas V Sekolah Dasar - Risma Wahyu Yuniatama; Intan Susetyo Kusumo Wardhani; Wahyu Nugroho (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The numeracy skills of elementary school students were relatively low. Based on observations and interviews conducted at SDN 2 Puru, SDN 1 Puru, and SDN 2 Suruh, students had difficulties understanding mathematical symbols, tended to memorize concepts, and experienced difficulties in solving word problems related to daily life. This study aimed to develop Mastery Peak-based Question Card media to improve the numeracy skills of fifth-grade elementary school students and examine its feasibility and effectiveness. The study employed the Research and Development (R&D) method using the ADDIE model, which included analysis, design, development, implementation, and evaluation. The uniqueness of the developed media lay in the integration of interactive Question Cards with the Mastery Peak feature, providing adaptive game-based practice and making learning more active, enjoyable, and meaningful than previous media. The results showed that the media was highly feasible based on expert validation scores of 95% from media experts, 93.75% from material experts, 78% from language experts, and 95% from practitioners. The independent t-test showed a significant improvement between the pre-test and post-test scores (p < 0.05). The N-Gain score was 63.5203, categorized as moderately effective. Therefore, the Mastery Peak-based Question Card media effectively improved elementary school students' numeracy skills.